Relationship between Menstrual Profile and Psychological Stress with Dysmenorrhea - Maryam Maryam; Mulyanusa Amarullah Ritonga; Istriati Istriati (Althea Medical Journal, 2016)
Background: Dysmenorrhea or menstrual cramps is the most common menstrual complaint among reproductive women in developing countries. The prevalence of dysmenorrhea is ranged from 19–91%. Many studies showed that factors associated with dysmenorrhea include a younger age, nulliparity, family history of dysmenorrhea, prolonged menstrual duration, high menstrual flow, psychological factors, and lifestyle. The objective of this study was to compare female medical students with dysmenorrhea and without dysmenorrhea regarding menstrual profile and psychological stress, also to examine the relationship between psychological stress and dysmenorrhea specifically..Methods: This cross-sectional study was conducted among 136 fourth year female medical students of Universitas Padjadjaran. It used a structured, self-assessment, validated, and reliable questionnaire, such as Wong Baker Faces® Pain Rating Scale in combination with Numeric Scale Pain, and Depression, Anxiety, Stress Scale (DASS-42). Then, the descriptive data analysis and chi-square hypothesis test were used to explore the relationship between the severity of psychological stress and the presence or severity of dysmenorrhea.Results: Family history of dysmenorrhea had a strongest relationship with dysmenorrhea. Nevertheless, there was no statistically significant interaction between the severity of stress and the presence of last menstrual cramps (p 0.745, Odd Ratio 1.15, 95% Confidence Interval 0.5–2.66). However, a positive relationship between the severity of stress and dysmenorrhea in last menstruation was found in this study (p 0.033, Odd Ratio 3.69, 95% Confidence Interval 1.06–12.8).Conclusions: The severity of stress and dysmenorrhea in last menstruation is related among the subjects with dysmenorrhea. [AMJ.2016;3(3):382–7]DOI: 10.15850/amj.v3n3.884